Education services and resilience processes: Resilient Black South African students' experiences - Theron, Linda C.; Theron, Adam M.C. (Children and youth services review, 2014)
The resilience literature is increasingly drawing attention to formal service provision as a means for social ecologies to support children's and youths' positive adjustment to challenging life circumstances. This article interrogates the universality and simplicity of this argument. Using a secondary data analysis of the life stories of 16 resilient, Black South African students from impoverished families, we show that education services predominated students' childhood and youth experience of formal support and that there was scant experience of other formal services. We theorise that contextual and cultural specifics informed the dominance of education services. However, this service did not consistently facilitate resilience processes. When it did, education services were characterised by active teacher–community connectedness and student responsiveness. Moreover, education service providers (i.e., teachers and principals) engaged in supportive actions that went beyond the scope of typical teacher tasks. Thus, we suggest that formal service facilitation of resilience processes is complex. It requires collaborative activity that might well demand atypical service acts. •Education services matter for the resilience of Black South African children/youth.•At times, education services heightened student vulnerability.•Constructive education service required active teacher–community–youth collaboration.•To support resilience, teachers engaged in typical and atypical teacher tasks.•Student emphasis on education services aligned with education's cultural salience.